Genome-Wide Identification of Target Genes for the Key B Cell Transcription Factor Ets1 - Saelee, Prontip; Kearly, Alyssa; Nutt, Stephen L.; Garrett-Sinha, Lee Ann (Frontiers in Immunology, 2017)
Background: The transcription factor Ets1 is highly expressed in B lymphocytes. Loss of Ets1 leads to premature B cell differentiation into antibody-secreting cells (ASCs), secretion of autoantibodies and development of autoimmune disease. Despite the importance of Ets1 in B cell biology, few Ets1 target genes are known in these cells. Results: To obtain a more complete picture of the function of Ets1 in regulating B cell differentiation we performed Ets1 ChIP-seq in primary mouse B cells to identify >10,000 binding sites, many of which were localized near genes that play important roles in B cell activation and differentiation. Although Ets1 bound to many sites in the genome, it was required for regulation of less than five percent of them as evidenced by gene expression changes in B cells lacking Ets1. The cohort of genes whose expression was altered included numerous genes that have been associated with autoimmune disease susceptibility. We focused our attention on four such Ets1 target genes Ptpn22, Stat4, Egr1 and Prdm1 to assess how they might contribute to Ets1 function in limiting ASC formation. We found that dysregulation of these particular targets cannot explain altered ASC differentiation in the absence of Ets1. Conclusions: We have identified genome-wide binding targets for Ets1 in B cells and determined that a relatively small number of these putative target genes require Ets1 for their normal expression. Interestingly, a cohort of genes associated with autoimmune-disease susceptibility are among those that are regulated by Ets1. Identification of the target genes of Ets1 in B cells will help provide a clearer picture of how Ets1 regulates B cell responses and how its loss promotes autoantibody secretion.